O protagonismo das crianças nas práticas educativas da educação infantil: investigando com as crianças da pré-escola - Dal Soto, Diana Vandréia (2014)
In recent decades, studies aimed at children and early childhood education have emphasized the need for and the importance of the active participation of children, both in the polls as in other social practices of which are part. In this line of thought, the school is designed as important cultural locus in the lives of children, which requires create pedagogical interventions which respect their rights of participation for the sake of quality early childhood education. In this sense, the present investigation, linked to the master course of the graduate program in education at the Federal University of Santa Maria, in the line of School Practices and public policies (LP2) and the Group research and Contemporary Studies in education and childhood-GIECEI, sought to understand what conditions is the involvement of children in school practices of early childhood education. Through listening to the children, analyze the conditions for child protagonist in the practices of the school of childhood and understand the place of the child in the planning of these practices. The investigative route assumes precepts of qualitative research and theoretical foundations search – Historical – Cultural theory methodology, more precisely in the work of Vygotsky. The data were produced from the insertion of the researcher in a preschool class of a Municipal School of early childhood education, located in the city of Santa Maria, in the State of Rio Grande do Sul - Brazil. The instruments of production data include observations of the interactions of children with the educational context, with its peers and with the teacher. From filmic and photographic records accompanied by annotations in field notebook. The investigation of the experiences of children as protagonists showed their perceptions about everyday life at school, similarly how are competent to participate actively in the (co)construction of educative context which are part. It was pointed out, in turn, the need of listening attentively by the teacher (a) seeking dialogue with the ' voices ' of children in its different expressions and manifestations to, thus building a quality education that responds to the interests, desires and needs of small, recognizing them as protagonists participation initiatives of these practices.